The Conception of National Insights in Islamic Perspective - Koko Adya Winata; Tatang Sudrajat; Muhibbin Syah; Asep Nursobah (Randwick International of Social Science Journal, 2020)
This article aims to explain the concept of national insight from an Islamic perspective. This research uses a descriptive qualitative method by collecting data through observation, documentation, and literature review. Based on the research results, the concept of national insight has been regulated and explained in Islamic teachings. National insight is a person's view of a national entity based on certain territorial boundaries that affect his attitude towards love for his homeland. As a religion of Rahmat Lil Alamin, Islam clearly states about human life formed in a diverse civilization, both in culture, ethnicity, religion, and Nation. Nationality is a reality of human civilization recognized in Islamic teachings as part of Allah's will in creating humans. The results of the research conclude: 1) The reality of the creation of human beings with nationalities and tribes is a necessity which is mentioned in the Koran, 2) The concept of nationality does not contradict Islamic teachings, 2) The Medina Constitution is a concept of a state carried out by the Prophet and Muslims who are in harmony with national values.